A STUDY ON THE APPLICATION OF VIRTUAL REALITY TECHNOLOGY FOR BASIC CHINESE LANGUAGE LEARNING: AN EDUCATIONAL ECONOMICS ANALYSIS - Chada Triamvithaya; Aree Roonprasang; Watcharin Kongpiboon; Thanyod Lopattananont (Journal of Industrial Education, 2025)
This article examines the application of Virtual Reality (VR) technology in introductory Chinese language learning through the lens of educational economics. Drawing on human capital theory and cost–benefit analysis, it investigates how VR can enhance learning efficiency, improve the cost-effectiveness of educational investment, and generate long-term returns. The study highlights VR-based learning environments such as virtual marketplaces, immersive classrooms, and cultural simulations designed to foster listening, speaking, and cultural understanding. Case studies, including Duolingo VR modules and Peking University's Virtual Chinese Cultural Tour, illustrate the potential and challenges of integrating VR into language education. The economic analysis highlights both the initial costs of VR hardware, software development, and instructional design, as well as the significant benefits, including reduced learning time, lower costs associated with overseas study, and increased labor market competitiveness. Despite the promising outcomes, barriers such as high initial investment and digital divide issues are acknowledged. The article concludes that VR represents a high-potential investment in education, aligning with economic theories that view education as a means of enhancing human capital. Future implications for the development of accessible VR educational ecosystems are also discussed, providing recommendations for policymakers, educational institutions, and technology developers.
Keywords: Online Learning and Analytics; Virtual Reality Applications and Impacts